2021
DOI: 10.1039/d0ta11302f
|View full text |Cite
|
Sign up to set email alerts
|

Surface and interface engineering for highly efficient Cu2ZnSnSe4 thin-film solar cells via in situ formed ZnSe nanoparticles

Abstract: In situ formed ZnSe NPs on the surface of CZTSe offer surface and interface engineering and provide a favourable band alignment between CZTSe and CdS leading to an improved device efficiency of 10.49%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Previous studies revealed that the W d value is a key parameter in determining charge separation and collection as well as influencing the conductivity of solar cells. 47,48 A wider W d is beneficial for collecting the photogenerated charge carriers in the long wavelength region near the band edge. This may also lead to reduced interface recombination or tunneling recombination, resulting in improved N a values in kesterite-based solar cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that the W d value is a key parameter in determining charge separation and collection as well as influencing the conductivity of solar cells. 47,48 A wider W d is beneficial for collecting the photogenerated charge carriers in the long wavelength region near the band edge. This may also lead to reduced interface recombination or tunneling recombination, resulting in improved N a values in kesterite-based solar cells.…”
Section: Resultsmentioning
confidence: 99%
“…determining charge separation and collection as well as inuencing the conductivity of solar cells 47,48. A wider W d is benecial for collecting the photogenerated charge carriers in the long wavelength region near the band edge.…”
mentioning
confidence: 99%
“…Building upon research efforts on other photovoltaic technologies, the application of passivation strategies along with the optimization of the active layer morphology and device architecture might mitigate the pernicious effects of short carrier lifetimes, as was achieved, for example, in Cu 2 ZnSnSe 4 and Sb 2 Se 3 solar cells. [ 134–136 ] The elimination of defects by introducing additives and/or dopants is also likely to be an effective approach, as has been already demonstrated when LiTFSI and alkaline‐earth metals were applied to silver pnictohalide solar cells to achieve significantly improved V oc values. [ 79,80,116 ] Similarly, partial cationic/anionic and HI‐assisted modification strategies have been demonstrated to improve the short‐circuit current density.…”
Section: Applicationsmentioning
confidence: 99%
“…25,42 Under this condition, the role of the inevitable Zn(S,Se) secondary phase in the CZTSSe solar cell performance is closely dependent on its location. 43–46 Furthermore, the classic bandgap gradient structure across the CIGSSe films through adjusting the [Ga]/([Ga] + [In]) ratio cannot be implemented in CZTSSe absorbers by tailoring cation composition. 47,48 This further aggravates the difference in the device performance, although the strategies of external cation substitution and alloying have been broadly employed to regulate the bandgap, 14,49–53 and there is still much work left to be done.…”
Section: Introductionmentioning
confidence: 99%